A teoria da localização industrial e o Programa Paulista de Arranjos Produtivos Locais: limites do modelo de competitividade no plano regional (2002 a 2012) - Nogueira, Rodrigo Hisgail de Almeida (2015)
Motivated to evaluate the contribution of Local Productive Systems (LPSs) for the development of the localities in which they were implemented in the State of São Paulo, this study sought to prove based on the analysis of some of the leading authors of the theory of industrial location, in first, if this theory is the main theoretical support base for formulating the development program the Local Productive Systems in Brazil, particularly in the state of São Paulo experience . In the mid-2000s , before a change in the framework of international economic order, with the advent of neo-liberal assumptions, degradation of the Brazilian industrial base , and deterioration of the social relations of production in urban areas, great hope is putted on clusters as endogenous growth promoter and promotion of territoriality in which it operates , as of successful international experiences of the industrial districts of the Third Italy , and high-tech Silicon Valley and Route 128 districts , both in the US . From the processing and analysis data selected on the São Paulo LPSs Program and especially the case study on the implementation of clusters in the Greater ABC Region , it was found that despite the contributions , regional competitiveness as a development proposal is insufficient and not alone serve the needs and social interests historically determined in this region